2020
DOI: 10.3389/fimmu.2020.00987
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Surgical Stress Promotes Systemic Immunothrombosis That Results in Distant Organ Injury

Abstract: Innate immunity can initiate platelet activation during the development of thrombosis through a process, termed immunothrombosis. Neutrophils form neutrophil extracellular traps (NETs) that have been shown to interact directly with platelets and play pro-coagulant roles in a variety of infectious and sterile inflammatory settings. Hepatic surgical stress initiated by ischemia/reperfusion (I/R) injury has wide systemic consequences on distant organs. However, the mechanisms of this remote injury phenomenon are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…It is well known that target autophagy is just an indirect way of regulating NETs formation. DNase has been widely employed in controlling inflammatory diseases via NETs degradation directly 41 . In our study, blocking NETs by DNase treatment significantly suppressed bacterial pneumonia‐mediated metastasis enhancement but has no effects on other subjects, which demonstrated that the NETs formation by bacterial infection was the key event related to cancer metastasis enhancement (Figure 6).…”
Section: Discussionmentioning
confidence: 53%
“…It is well known that target autophagy is just an indirect way of regulating NETs formation. DNase has been widely employed in controlling inflammatory diseases via NETs degradation directly 41 . In our study, blocking NETs by DNase treatment significantly suppressed bacterial pneumonia‐mediated metastasis enhancement but has no effects on other subjects, which demonstrated that the NETs formation by bacterial infection was the key event related to cancer metastasis enhancement (Figure 6).…”
Section: Discussionmentioning
confidence: 53%
“…It should be noted that, in addition to our observation of a likely influence of platelet activation on neutrophil phenotype, it is also probable that neutrophil polarization to the CXCR4 hi phenotype may also influence platelet activation. Activated neutrophils are known to release several soluble platelet-activating mediators 34 , and, while we did not evaluate NET generation by the CXCR4 hi neutrophils, stimulation of neutrophil CXCR4 expression with a low dose of lipopolysaccharide has been associated with the release of NETs, which in turn have documented platelet activating and thromboinflammatory effects 35,36 .…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, as established recently, NETs can contain suppressor molecules (e.g., PD-L1) and have a negative effect on the activity of cytotoxic lymphocytes ( Fig. 2, II ) [ 49 ]. A specific role in the study of NETs should be assigned to work on the treatment of cancer pathologies with the help of re-programmed T cells with induced cytolytic activity.…”
Section: The Role Of Nets In Tumor Processesmentioning
confidence: 92%